Multi - Objective Genetic Algorithm based Study for Energy Efficient Routing in MANET - Jain, Arpit Kumar; Kumar, Manish (International Journal of Computer Sciences and Engineering, 2019)
Mobile Ad hoc Networks (MANET) possess dynamic topology and have no fixed infrastructure. Numerous challenges in routing in MANETs exist because of its frequent and unpredictable topology. One of the major constraints in designing of these protocols is the battery power. Various routing protocols have been implemented for finding optimal path from source to destination considering the cost and efficient use of energy. This paper explores different types of routing protocols, their merits and demerits, approach of routing protocols and implementation of one such energy efficient routing protocol technique using Genetic Algorithm to determine the shortest path between the source and the destination. Routing protocols based on Genetic Algorithm gives us the insight that how the concepts of genetics are applied to MANETs and is used to determine an optimal route taking into account the optimization of battery power. Genetic Algorithm takes less computational time, provides multiple optimal paths in case of failure of one path as well as increases the throughput of the network. In addition it covers the significance of Genetic Algorithm in MANETs.